Cyclic regulation of Trpm4 expression in female vomeronasal neurons driven by ovarian sex hormones - Eckstein, Eugenia; Pyrski, Martina; Pinto, Silvia; Freichel, Marc; Vennekens, Rudi; Zufall, Frank (Molecular and cellular neuroscience, 2020)
The vomeronasal organ (VNO), the sensory organ of the mammalian accessory olfactory system, mediates the activation of sexually dimorphic reproductive behavioral and endocrine responses in males and females. It is unclear how sexually dimorphic and state-dependent responses are generated by vomeronasal sensory neurons (VSNs). Here, we report the expression of the transient receptor potential (TRP) channel Trpm4, a Ca2+-activated monovalent cation channel, as a second TRP channel present in mouse VSNs, in addition to the diacylglycerol-sensitive Trpc2 channel. The expression of Trpm4 in the mouse VNO is sexually dimorphic and, in females, is tightly linked to their reproductive cycle. We show that Trpm4 protein expression is upregulated specifically during proestrus and estrus, when female mice are about to ovulate and become sexually active and receptive. The cyclic regulation of Trpm4 expression in female VSNs depends on ovarian sex hormones and is abolished by surgical removal of the ovaries (OVX). Trpm4 upregulation can be restored in OVX mice by systemic treatment with 17 beta-estradiol, requires endogenous activity of aromatase enzyme, and is strongly reduced during late pregnancy. This cyclic regulation of Trpm4 offers a neural mechanism by which female mice could regulate the relative strength of sensory signals in their VSNs, depending on hormonal state. Trpm4 is likely to participate in sex-specific, estrous cycle-dependent and sex hormone-regulated functions of the VNO, and may serve as a previously unknown genetic substrate for dissecting mammalian sexually dimorphic cellular and behavioral responses.